2008
DOI: 10.1144/1467-7873/07-144
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic distribution in mesquite ( Prosopis laevigata ) and huizache ( Acacia farnesiana ) in the Zimapán mining area, México

Abstract: Arsenic concentrations have been determined in mesquite ( Prosopis laevigata ) and huizache ( Acacia farnesiana ) growing on As-rich soils in the semi-arid mining area of Zimapán, México. The elevated As contents in the substrates (up to 32 000 mg/kg) were reflected in the dry weight concentrations of twigs (up to 82.7 mg/kg in mesquite and 225 mg/kg in huizache), and leaves (up to 78.2 mg/kg in mesquite and 67.0 mg/kg in huizache). Arsenic concentrations in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
3
8
0
9
Order By: Relevance
“…The control zone was in the normal concentration range for soil for the following elements: Pb, Zn, Cu, Cd (2–300, 1–900, 2–250, and 0.01–2.0 mg kg −1 , respectively) according to Alloway () and As (0.1–40 mg kg −1 ) according to Bowen (), it was therefore considered suitable to be taken for comparison with the other polluted sites. Comparing our data with other studies (Armienta et al, ; Franco‐Hernández et al, ; Morton‐Bermea et al, ; Ruíz and Armienta, 2012; Santos‐Jallath et al, ), it is clear that metal concentrations in the mining waste vary widely, which is associated with mining and smelting operations as well as the type of mineral resources (Bradshaw, ). Based on the results, it can be observed that the soils are a source of contamination that could affect the development of organisms that grow and live on them.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The control zone was in the normal concentration range for soil for the following elements: Pb, Zn, Cu, Cd (2–300, 1–900, 2–250, and 0.01–2.0 mg kg −1 , respectively) according to Alloway () and As (0.1–40 mg kg −1 ) according to Bowen (), it was therefore considered suitable to be taken for comparison with the other polluted sites. Comparing our data with other studies (Armienta et al, ; Franco‐Hernández et al, ; Morton‐Bermea et al, ; Ruíz and Armienta, 2012; Santos‐Jallath et al, ), it is clear that metal concentrations in the mining waste vary widely, which is associated with mining and smelting operations as well as the type of mineral resources (Bradshaw, ). Based on the results, it can be observed that the soils are a source of contamination that could affect the development of organisms that grow and live on them.…”
Section: Discussionsupporting
confidence: 79%
“…In general, in Mexico there are few studies that assess the concentration of heavy metals in substrates and plants growing in mining waste (Armienta et al, ; Carrillo‐Gonzalez, ; Carrillo‐González and González‐Chávez, ; Díaz‐Villaseñor, ; Flores‐Tavison et al, ; Franco‐Hernández et al, ; Juárez‐Santillan et al, 2010; Prieto‐García et al, ; Puga et al, ; Ruiz and Armienta, ; Santos‐Jallath et al, ), as well as the identification of heavy metals inside plants tissues. These studies allow to observe the presence of metals, becoming evident the accumulation and translocation to different organs of the plant, using tools as optic and scanning microscopy or energy dispersive X‐ray spectrometry (Arias et al, ; Günthardt‐Goerg and Vollenweider, ; Meyers et al, ; Tung and Temple, ; Vieira et al, ; Vollenweider and Günthardt‐Goerg, ; Vollenweider et al, b).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, uses of Prosopis spp in the bioremediation process have been reported. In this regard, Armienta et al (2008) reported that mesquites are not hyperaccumulators, but are in fact As-tolerant plants and can therefore be considered as an option for a remediation program to stabilize eroding tailings. On the other hand, Haque et al (2008) mentioned that mesquite plants have developed a variety of physiological and molecular mechanisms for growth in, and adaptation to, arid zones.…”
Section: Introductionmentioning
confidence: 99%
“…En México se han realizado inventarios florísticos de plantas que crecen en sitos contaminados por metales pesados (Cuadro III). En el análisis destacan algunas especies como Prosopis leavigata y Acacia farnesiana, las cuales son especies obligadas en lugares contaminados de zonas áridas y semiáridas, capaces de acumular en tallo hasta 87 y 225 mg/kg de arsénico, respectivamente (Armienta et al 2008).…”
Section: Especies Vegetales Acumuladoras De Metales En Méxicounclassified